Analysis of The Relationship Allergic Contact Dermatitis on Scavengers - Wiratama, Rifki; Hary Cahyati, Widya; Laksono, Budi (Public Health Perspective Journal, 2020)
Occupational skin disease is the second most common occupational disease in Europe after musculoskeletal injuries, while the most common occupational skin disease is contact dermatitis, accounting for 70-90%. Determining the cause of contact dermatitis in the work environment is very important, because avoiding the causative agent will lead to a cure and reduce the recurrence rate. This study aims to analyze the relationship between personal hygiene, knowledge, use of personal protective equipment, and working period of allergic contact dermatitis in scavengers at the Piyungan Yogyakarta garbage dumpsite. This type of research is an observational analytic study with a cross sectional design. The research sample was 112 scavengers. The analysis of this research uses Path Analysis. The results showed that there was a direct relationship of personal hygiene to allergic contact dermatitis with a path coefficient of 0.243 (p = 0.003 <0.05), there was a direct relationship of knowledge of allergic contact dermatitis with a path coefficient of 0.216 (p = 0.000 <0.05), There was a correlation between the use of PPE on allergic contact dermatitis with a path coefficient of 0.124 (p = 0.001 <0.05). There was a relationship between working period and allergic contact dermatitis with a path coefficient of 0.253 (p = 0.000 <0.05). Scavengers should increase knowledge about allergic contact dermatitis, especially regarding the impact and prevention of allergic contact dermatitis and pay more attention to regular individual hygiene.